The complete chloroplast genome of Aster sampsonii (Hance) Hemsl, a perennial herb - Qinxiang Chang; Yan Li; Pengguo Xia; Xiang Chen (Mitochondrial DNA. Part B. Resources, 2021)
Aster sampsonii (Hance) Hemsl is endemic to China. The complete chloroplast genome of Aster sampsonii was studied here. The genome was 152,686 base pair (bp) in length, containing a large single-copy (LSC) region of 84,345 bp, a small single-copy region (SSC) of 18,249 bp and a pair of inverted repeats (IRs) of 25,046 bp. It contains 132 unique genes, including 86 protein-coding genes, 36 transfer RNA (tRNA) genes, and eight ribosomal RNA (rRNA) genes. The GC content of the complete chloroplast genome sequence was 37.3%. Phylogenetic analyses using complete chloroplast genomes showed that Aster sampsonii is most closely related to Aster hypoleucus (NC_046503.1).